Concurent fatal helm1nthosis and balantidos1s in red monkey (Erythrocebuspatas) in Ibadan, Nigeria (2002)
Fresh fecal specimen from a moribund red monkey (Erythrocebuspatas) from the zoological garden, University of Ibadan with a history of dysentery was examined. Ova of Triclmris spp., Enterobius spp, Ancylostoma spp. and Strongyloides spp., as well as Balantidium spp oocysts were found. Post mortem, findings revealed the large intestine heavily infected with worms especially Trichuris spp., Ancylostoma spp. and Trichostronglus spp. which were enmeshed in a thick layer of mucous and blood on the mucosa. The public health importance is discussed.